Effect of heat treatment on the tribological properties of Nickel-Boron electroless coating - Arias Torres, Sandra Milena; Gómez Botero, Maryory Astrid; Correa Bedoya, Esteban; Echeverría Echeverría, Félix; Castaño Gonzalez, Juan Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 101-110).